PENGARUH KONSENTRASI KOH PADA PROSES EKSTRAKSI RUMPUT LAUT (Kappaphycus alvarezii) TERHADAP SIFAT ALKALI TREATED COTONII (ATC) - Marsanda Rizka Fauziah; Arif Rahman Hakim; RR. Juni Triastuti (Universitas Muhammadiyah Gresik, 2024)
One of the superior fishery commodities abundant in Indonesian waters is Kappaphycus alvarezii seaweed. The seaweed type K. alvarezii can be used to make Alkali Treated Cottonii (ATC), a raw material for carrageenan. Making ATC goes through seaweed extraction stages, which can be done using conventional methods. Data collection for this research was carried out using observation, interviews, and active participation. The results of ATC processing using conventional methods and variations of KOH show that the administration of KOH affects the quality of the ATC product; the higher the ATC, the higher the yield percentage and temperature produced by the extract solution. The best use of KOH is in the treatment with a KOH concentration of 8%, a water content of 13.73%, a yield of 73.62%, and a temperature of 58.15%.